The Twisted Transfer Variety (Communications in Mathematical Research, 2019)
In this paper, we describe the variety defined by the twisted transferideal. It turns out that this variety is nothing but the union of reflecting hyperplanesand the fixed subspaces of the elements of order $p$ in $G$.